Validity and reliability of the WIMU® system to measure barbell velocity during the half-squat exercise - Garcia-Pinillos, F.; Latorre-Román, P. A.; Valdivieso-Ruano, F.; Balsalobre-Fernández, C.; Párraga-Montilla, J. A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
This study aimed at determining the reliability and concurrent validity of the WIMU® system when measuring barbell velocity during the half-squat exercise by comparing data with the gold standard. A total of 19 male competitive powerlifters performed an incremental loading test using the half-squat exercise. The mean velocity, mean propulsive velocity and maximum velocity of all repetitions were recorded through both WIMU and T-Force systems. As a measure of reliability, coefficient of variations ranged from 6%-17% and standard error of means ranged from 0.02-0.11 m/s, showing very close reliability of data from both devices. Validity, in terms of coefficient of correlations and pairwise comparisons, was also tested. Except for some relative loads, the Pearson correlation analysis revealed significant correlations between both devices for mean velocity, mean propulsive velocity and maximum velocity (r > 0.6, p < 0.05). The mean velocity, mean propulsive velocity and maximum velocity were underestimated for the WIMU system compared to T-Force data at some points of the load-velocity relationship. The linear regression models performed revealed a strong load-velocity relationship in the half-squat exercise for each individual using mean velocity, mean propulsive velocity and maximum velocity, regardless of the instrument used (R2 > 0.77 in all cases). Bland-Altman plots revealed low systematic bias (=0.06 m s-1) and random error (=0.07 m s-1) for the mean velocity and mean propulsive velocity obtained from the WIMU system as compared to the T-Force, while the maximum velocity resulted in an underestimation by the WIMU system (-0.16 m s-1) as compared to the linear position transducer system. The results indicate that the WIMU system is a reliable tool for tracking barbell velocity in the half squat, but these data also reveal some limitations regarding its concurrent validity as compared to the gold standard, with velocity measures slightly underestimated in the tested conditions.